In vitro digestion of oil-in-water emulsions stabilized by whey protein nanofibrils. (September 2017) - Mantovani, Raphaela Araujo; Pinheiro, Ana Cristina; Vicente, António Augusto; Cunha, Rosiane Lopes
Abstract: The effect of pH (3 and 7) and varied energy density of a high-pressure homogenization process on the stability of oil-in-water (O/W) emulsions stabilized by whey protein fibrils was evaluated. A dynamic digestion model comprising the simulation of stomach, duodenum, jejunum and ileum, has been used to evaluate O/W emulsions' behavior under gastrointestinal (GI) conditions. The emulsions did not separate phases during the storage period (7 days). The emulsions stabilized by whey protein fibrils were stable under simulated gastric conditions but were destabilized in the simulated intestinal conditions. In a similar way, the whey protein fibrils' dispersion showed a high resistance to proteolytic in vitro digestion by pepsin (gastric stage) but was more readily degraded by pancreatin (intestinal stage). This fact confirms the significant impact of the interfacial characteristics on emulsions' digestion. The percentage of free fatty acids (FFA) absorbed in the simulated intestinal conditions (jejunum and ileum) was much lower than the total percentage of FFA released due to the use of WPI fibrils as emulsifier. This work contributes to a better understanding about the behavior of O/W emulsions stabilized by whey protein fibrils within the GI tract; this knowledge is fundamental when considering the final application of this protein in food products. Graphical abstract: Highlights: WPI fibrils showed emulsifying/stabilizing properties WPI fibrils provided kinetically stable emulsions Emulsion with WPI fibrils destabilized only under simulated intestinal conditions FFA absorbed was much lower than total percentage of FFA released under simulated intestinal conditions